Kajian Aktivitas Hg Dalam Tanah dan Jaringan Tanaman Pada Tanah Tercemar Logam Merkuri Dengan Pemberian Bahan Organik Pada Kedalaman yang Berbeda - Rully Akbar; Saiful Darman; Uswah Hasanah (Universitas Tadulako, 2018)
This study aims to understand the interaction Award kirinyu Bokashi (Chromolaena odorata L.) with increasing doses of various soil layers into terhadapat activity Hg in soil solution and plant uptake. This research has been carried out glass house Department of Agriculture Faculty of Agriculture, University Tadulako. This research was made up of two factors in a factorial design with environmental design is the design of each perlukuan repeated 3 times. Sehinggah which there are 3 x 4 x 3 = 36 experimental units. The parameters observed in the study is the analysis of the soil after harvest includes an analysis of soil chemical properties include C-organic, CEC, pH, Hg soil and Hg plant tissue This study also shows that, with the provision of Bokashi kirinyu on Waste Tailings very significant effect on the concentration of mercury in soil and plant tissue and soil reaction or pH of the soil, and the C-Organic Cation Exchange Capacity (CEC).